SOCIOLINGUISTIC PERSPECTIVES ON DIGITAL SLANG AND INTERNET NEOLOGISMS IN CONTEMPORARY ENGLISH (Ustozlar uchun, 2026)
The rapid digitalization of global communication has catalyzed an unprecedented evolution within the contemporary English lexicon. This paper investigates the sociolinguistic dynamics of digital slang and internet-driven neologisms, examining their transition from ephemeral online jargon to stabilized, institutionalized lexical units. By analyzing the morphological structures, semantic shifts, and sociolinguistic mechanisms occurring across prominent social media ecosystems (such as TikTok, X, and Instagram), the study explores how digital communication challenges traditional, prescriptive linguistic hierarchies. The research employs a descriptive linguistic approach to highlight the shift from traditional linguistic norms toward a fluid, structurally complex, and globally democratized understanding of modern English. Furthermore, the paper addresses the lexicographical implications of this shift, demonstrating how digital slang redefines identity, in-group solidarity, and global cultural capital.